Susceptibility of Culex quinquefasciatus, the Vector of Lymphatic Filariasis, to Few Conventional and Newer Insecticides in Different Parts of Rajasthan - Singh, Karam V; Bansal, S K (Annals of Arid Zone, 2016)
Studies on the current insecticide susceptibility status of Culex quillquefascialllsagainst few conventional insecticides, i.e., DOT and Dieldrin, and morepotent ones, i.e., malathion, fcnitrothion, propoxur and permethrin, were carriedout in three desert districts (Barmer, Jodhpur and Pali) and three non-desert districts(Ajmer, Kota and Udaipur) in Rajasthan. The results of the investigations revealedthat this vector species was no longer susceptible to any of the tested insecticides.In desert districts, the species exhibited resistance to DOT, dieldrin and malathion(mortalities